2015
DOI: 10.1590/1678-775720140243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the magnetic field on microorganisms in the oral cavity

Abstract: Since the beginning of their lives, all living organisms are exposed to the influence of geomagnetic fields. Objectives: With respect to the positive effects that magnetic fields have on human tissues, especially the bactericidal effect, this investigation aimed to assess their influence on the reduction of oral microorganisms.Material and Methods : In order to obtain adequate specimens of dental plaque deposit, microbes such as Streptococcus parasanguinis, Staphylococcus epidermidis, Rhodococcus equi and Cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
2
23
0
1
Order By: Relevance
“…The patients were instructed to use moist brush without any dentifrices in cleaning abutments to eliminate an expected effect of dentifrices on oral microflora as reported by Haffajee AD et al 2001 (11) and Brkovic et al 2015 (8) . Patients were also motivated to avoid usage of antibiotics minimum one week before bacterial samples collection as this could affect the crevicular bacterial flora Walker et al 1981 (38) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients were instructed to use moist brush without any dentifrices in cleaning abutments to eliminate an expected effect of dentifrices on oral microflora as reported by Haffajee AD et al 2001 (11) and Brkovic et al 2015 (8) . Patients were also motivated to avoid usage of antibiotics minimum one week before bacterial samples collection as this could affect the crevicular bacterial flora Walker et al 1981 (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Follow up period were formulated not to exceed one month after magnet fixation to avoid an expected effect of corrosive surrounding media on dental magnets as concluded by Chung C H, et al 2005 (10) Moreover, Boeckler et al 2009 (8) stated according to ISO 10271 that modern magnetic attachment showed metal ions dissolved in all corrosive medium specimen within few weeks of use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most attractive area of application of possible magnetic effects is medicine because some bacteria are infection agents, pathogens. For this reason, numerous investigations focused on inhibition of pathogens by different types of applied magnetic fields [Segatore et al, ; Ahmed et al, ; Fijałkowski et al, ; Bayır et al, ; Brkovic et al, ]. These data describe applications of strong static magnetic fields or strong alternating magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms have adapted to fluctuations in the Earth's magnetic field over a period of time. However, the response of bacteria to other external magnetic field influences is still being investigated (Brkovic, Postic, & Ilic, 2015;Kohno, Yamazaki, Kimura, & Wada, 2000). In space, humans encounter a different environment of radiation and electromagnetic forces.…”
mentioning
confidence: 99%